(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
In recent years, education has been changing rapidly due to technological development. One of the most influential innovations is artificial intelligence (AI). While AI is often associated with robotics or advanced computing, it is now becoming an essential tool in classrooms, especially in language learning. In English language classes, assessment plays a crucial role in measuring students’ progress. However, traditional assessment methods can be time-consuming and sometimes subjective. For this reason, the use of artificial intelligence in evaluating students’ performance has become increasingly important.